Application of monte carlo simulation in financial model - 494797 Leong, Mei Yen; Yeak, Su Hoe, 1971-; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2007